Assessing the Economic Impact of Forest Management in the Brazilian Amazon Through Real Options Analysis - Rocha, Qüinny Soares [UNESP]; da Silva, Richardson Barbosa Gomes [UNESP]; Munis, Rafaele Almeida [UNESP]; Simões, Danilo [UNESP] (MDPI, 2024)
Reduced-impact logging is a key aspect of sustainable forest management in the Brazilian Amazon. Real Options Analysis (ROA) improves the evaluation of certified projects, increases their value, and supports investor confidence. This study evaluates the economic viability of a forest management investment project in certified areas of the Brazilian Amazon, using ROA to incorporate uncertainty and managerial flexibility into the decision-making process. The analysis focused on an Ombrophilous Dense Forest in its first cutting cycle, with 30 species of diameter at breast height ≥ 50 cm and a projected activity period of 30 years. Timber value was modeled using the mean reversion motion, and a binomial decision model was applied, incorporating options such as deferral, abandonment, and interruption. The deferral option should be exercised with a 100% probability, both in the joint calculation scenario and in separate analyses, highlighting the significant value of this managerial flexibility. In addition, when analyzed using ROA, the value of the project increased by 105% (USD 91,784,176) compared to the traditional net present value approach. The forest management investment project in the Brazilian Amazon is economically viable and the application of ROA reveals significant value added, demonstrating the importance of incorporating flexibility into investment decisions.
Keywords: decision making; expanded net present value; investment projects; managerial flexibilities; timber products; volatility